1981
DOI: 10.1135/cccc19813270
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the distribution of platinum, its dispersion, and activity of catalysts prepared by impregnation of activated carbon with chloroplatinic acid solutions

Abstract: The effect was studied of the solvent of chloroplatinic acid used for impregnation of activated carbon on the distribution and dispersion of platinum and on the catalyst activity. Using different solvents, catalysts were prepared exhibiting either surface platinum distribution (water) or its uniform distribution (ketones). Catalysts with uniform platinum distribution displayed a better stability of the platinum dispersity against sintering. The catalyst activities in liquid phase hydrogenation of 1-octene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The difference of solvent effects on the metal deposition can also be characterized by the wetting heats of the support in corresponding solvents [33]. The results for supports A and B were obtained experimentally by using a solution-reaction isoperibol calorimeter [34] and presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The difference of solvent effects on the metal deposition can also be characterized by the wetting heats of the support in corresponding solvents [33]. The results for supports A and B were obtained experimentally by using a solution-reaction isoperibol calorimeter [34] and presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Once the GDL surface becomes hydrophilic, the plating bath with Pt ions can penetrate into the interior of the porous carbon layer, leading to a more uniform distribution throughout the carbon particles. 17,18 During electrodeposition, the thickness of the catalyst layer is controlled by the electrolyte penetration into the porous carbon layer of the GDL. This phenomenon depends on the hydrophilicity and surface energy of the GDL.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the methods employed to prepare catalysts have a considerable influence on the catalyst properties and activities. In fact, several research groups have investigated the factors that influence the various preparation stages [3,[10][11][12]. As an example, Machek et al [12] described the solvent affect on the adsorption of chloroplatinic acid and indirectly the Pt dispersion on activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several research groups have investigated the factors that influence the various preparation stages [3,[10][11][12]. As an example, Machek et al [12] described the solvent affect on the adsorption of chloroplatinic acid and indirectly the Pt dispersion on activated carbon. They found that polar solvents such as water resulted in sintering and a nonuniform distribution of Pt while less polar solvents such as ketone gave rise to a uniform distribution of the metal phase.…”
Section: Introductionmentioning
confidence: 99%